2012
DOI: 10.1186/1475-2859-11-132
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli to increase plasmid DNA production in high cell-density cultivations in batch mode

Abstract: BackgroundPlasmid DNA (pDNA) is a promising molecule for therapeutic applications. pDNA is produced by Escherichia coli in high cell-density cultivations (HCDC) using fed-batch mode. The typical limitations of such cultivations, including metabolic deviations like aerobic acetate production due to the existence of substrate gradients in large-scale bioreactors, remain as serious challenges for fast and effective pDNA production. We have previously demonstrated that the substitution of the phosphotransferase sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 40 publications
4
39
2
Order By: Relevance
“…This evidence agrees with the finding that genome replication in D. radiodurans RecA − strains is slower when compared with that observed in the wild-type counterpart [36]. Conversely, deletion of RecA does not significantly affect the growth rate of E. coli [55]. Moreover, it was demonstrated that the overexpression of recA decreases the rate of replication fork progression in E. coli [29], presumably by inhibiting αEc replisomes [28].…”
Section: Discussionsupporting
confidence: 86%
“…This evidence agrees with the finding that genome replication in D. radiodurans RecA − strains is slower when compared with that observed in the wild-type counterpart [36]. Conversely, deletion of RecA does not significantly affect the growth rate of E. coli [55]. Moreover, it was demonstrated that the overexpression of recA decreases the rate of replication fork progression in E. coli [29], presumably by inhibiting αEc replisomes [28].…”
Section: Discussionsupporting
confidence: 86%
“…It has previously been observed that an endA deletion strain exhibits increased plasmid DNA production in vivo, [27] but its role was not clear in vitro, as the endA deletion was previously assessed only in combination with recCBD deletion. [17] In CFPS reactions performed with extracts from source strains lacking endonuclease I (MCJ.495), we observed a greater than fourfold increase in sfGFP synthesis compared to that of rEc.E13.ΔprfA (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…pHN concentration was determined by extracting plasmid DNA with the Qiagen Spin Mini Prep kit (Hilden, Germany), following manufacturer instructions. The plasmid DNA concentration was determined at 260 nm using a Nanodrop UV spectrophotometer [27]. …”
Section: Methodsmentioning
confidence: 99%